Postsynaptic cleft density changes with combined exercise protocols in an experimental model of muscular hypertrophy - Neto, Jurandyr Pimentel [UNESP]; Rocha, Lara Caetano [UNESP]; Jacob, Carolina Dos Santos [UNESP]; Barbosa, Gabriela Klein [UNESP]; Ciena, Adriano Polican [UNESP] (PAGEPress Publications, 2021)
The vertical ladder-based protocols contribute to the NMJ junction's adaptations, and when combined with and without load, can be potentiated. The present study aimed to investigate postsynaptic regions of the biceps brachii muscle in adult male Wistar rats submitted to different vertical ladder-based protocols (Sedentary-S; Climbing-C; Climbing with Load-LC and Combined Climbing-CC). The protocols (C, LC, CC) were per-formed in 24 sessions, 3 x/week, for 8 weeks. The myofibrillar ATPase analysis showed an increase in cross-sectional area (CSA) of the muscle fibers Type I in all trained Groups; Type II in C and LC and reduction in CC; Type IIx higher in all trained Groups. In the postsynaptic cleft, the stained area presents smaller in Groups C, LC, and CC; the total area showed smaller than LC and higher in C and CC. The stained and total perimeter, and dispersion showed a reduction in C, LC, and CC, higher maximum diameter in Groups C and CC, and decreased in LC. Regarding the postsynaptic cleft distribution, the stained area presented a decrease in all trained Groups. The integrated density presented higher principally in CC. The NMJ count showed an increase in all trained Groups. We concluded that the vertical ladder-based protocols combined contributed to the post-synaptic region adaptations.
Keywords: Hypertrophy; Immunohisto-chemistry; Morphometry; Muscle fiber type; Neuromuscular junction; Synapse